The Effect of Debt Policy, Dividend Policy, Investment Decisions and Corporate Size on Corporate Value - Dewi, Ni Luh Putu Sandrya; Novitasari, Ni Luh Gde (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
Business development in the era of globalization requires all types and sectors of businesses to compete for survival. A company must implement a strategy that can improve its performance to achieve its goals. A company's value deals with the price a potential buyer would pay when the company is sold. This recent paper examines the impacts of debt policy, dividend policy, investment decisions, and corporate size on the values of IDX-listed manufacturing companies of 2018-2020. We purposively selected 69 manufacturing companies and conducted 207 observations. Research data were analyzed by a multiple linear regression test. The results suggest that debt policy, investment decisions, and company size has a partial effect on firm value. Also, dividend policy has no partial effect on company value.Â Keywords: Company Size, Debt Policy, Dividend Policy, Firm Value, Investment Decision.